Paleoturfa associada à evolução da drenagem/paisagem em uma vertente de vereda no Triângulo Mineiro - Melo Júnior, Heliomar Baleeiro de (2015)
This study was based on a sequence soil/paleosoil exposed by a profile cut on the side of a gully on the right side of creek Beija Flor, near its spring (19° 21 29,8 S e 47° 58 47,8 W), in the county of Uberaba, MG. The soil is classified as a Ustept, presenting Acric character and, at the 4th level, it is Plinthic, (Plinthic Acrustept ). The paleosoil refers to a paleoturf. The geomorphological events that marked the evolution of local landscape, among which the peat burial, the paleodrainage and the present drainage, the presence of polyciclic soils and the phytogeography, led to this study, recognizing past vegetation and its evolution present Day, as well as the climate/pedoclimate in such recent geological past. Thus, this study was, essentially directed to carbon dating and the carbon isotopic composition in the soil organic matter, in the paleoturf and in the dominant plants surrounding the study site. Samples of soil and paleoturf were collected every 10 or 20 cm with a cutting shovel and knife, until the depth of 380 cm, for the isotope analyses and for dating by the method of 14C. The soil/paleoturf profile was described morphologically, sampled and characterized according to its physical and chemical properties. Leaf samples of the most frequent plant species were collected in a radius of approximately 50 meters around the profile site. These plants were identified and subjected to characterization of isotope composition (δ 13C) and determination of total organic carbon (TOC) contents. The paleoturf base presented approximate age of 20,272 cal years BP (calendar years before the present, based on present as year 1950) while the estimated age for the top of the same turf was estimated in 16,636 cal years BP, indicating that, in the interval of approximately 3,636 years, conditions for peat formation (organosoil) were present, during the dominion of C4 photosynthesis cycle plants. After the period of peat burial by mineral sediments, hydromorphic conditions prevailed for a period long enough for gleyization of this material, which was also favorable for the domination of C4 plants. The time lapse in which drainage improved (deepening of the water table) and, consequently, C4 plants started to co-exist with C3 plants was, at least, 378 cal years BP. That is the period in which data show a 13C isotope enrichment in the soil organic matter, resulting from a more effective occupation by C3 plants. Presently, there is a vegetation of C3 and C4 cycle the profile, and δ13C varied from -30.23 , isotope value for the species Pterodon pubescens (Benth.) Benth., which is a typical Fabaceae from the cerrado, and is less rich in 13C by approximately 19 in relation to the most enriched plant species in 13C (-10,81 ), which is the isotope value of Elionurus sp., a typical Poaceae of hydrophilic regions, with C4 photosyntheis cycle.